Conditions of Seagrass Ecosystems in Ketapang Coastal Waters, West Lombok Regency: Kondisi Ekosistem Lamun di Perairan Pantai Ketapang Kabupaten Lombok Barat - Muh Fahruddin; Anita Prihatini Ilyas (Department of Aquatic Resources Management, Faculty of Fisheries and Marine Science, IPB University, 2023)
Ketapang coastal waters, West Lombok Regency is a coastal area where seagrass ecosystems are distributed, but so far there has been no research data explaining the condition of seagrass ecosystems. This study aims to determine the condition of the seagrass ecosystem in the coastal waters of Ketapang, West Lombok Regency. This research was conducted in November 2021 which is located in the coastal waters of Ketapang, West Lombok Regency. Sampling was carried out by purposive sampling method consisting of 3 observation stations. Seagrass samples were collected using line transects and quadrant transects measuring 50×50 cm2. The parameters observed included physical and chemical water quality, as well as seagrass density and coverage. The results of water parameter measurements are still at the threshold of water quality standards. The seagrass found were Enhalus acoroides, Thalassia hemprichii, Cymodocea rotundata, and Halophila ovalis. The highest seagrass density was at station 1, 407 shoots/m2, while the lowest density was at station 3, 211 shoots/m2. The condition of the highest seagrass cover was found at station 1 and the lowest cover was found at stations 2 and 3.